2021
DOI: 10.1177/1535370221991094
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic kinases as drivers of the epithelial-to-mesenchymal transition and as therapeutic targets against breast cancers

Abstract: Biological therapies against breast cancer patients with tumors positive for the estrogen and progesterone hormone receptors and Her2 amplification have greatly improved their survival. However, to date, there are no effective biological therapies against breast cancers that lack these three receptors or triple-negative breast cancers (TNBC). TNBC correlates with poor survival, in part because they relapse following chemo- and radio-therapies. TNBC is intrinsically aggressive since they have high mitotic index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 93 publications
(134 reference statements)
1
16
0
Order By: Relevance
“…According to pan‐cancer analysis, BUB1 may play important roles in interaction with the The anaphase‐promoting complex/cyclosome (APC/C) activator protein Cdc20, which has carcinogenic and prognostic significance 13 . Moreover, the overexpression of BUB1 proteins is strongly associated with the malignant phenotype and poor prognosis in various malignancies, including bladder cancer, osteosarcoma, leukemia, gastric cancer, liver cancer, breast cancer, and pancreatic ductal adenocarcinoma 14–20 . The above literature indicates that BUB1 may contribute to the progression of multiple human tumors through a variety of complex mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…According to pan‐cancer analysis, BUB1 may play important roles in interaction with the The anaphase‐promoting complex/cyclosome (APC/C) activator protein Cdc20, which has carcinogenic and prognostic significance 13 . Moreover, the overexpression of BUB1 proteins is strongly associated with the malignant phenotype and poor prognosis in various malignancies, including bladder cancer, osteosarcoma, leukemia, gastric cancer, liver cancer, breast cancer, and pancreatic ductal adenocarcinoma 14–20 . The above literature indicates that BUB1 may contribute to the progression of multiple human tumors through a variety of complex mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…One TTK inhibitor (CFI-402257) has been tested in BC cell lines and entered clinical trials [50,51]. Moreover, TTK is also considered a top target for radiosensitization as the inhibition of TTK could enhance the sensitivity to radiotherapy in many basal-like BC cell lines [52,53]. Jumonji C domain-containing demethylase 4 (JMJD4) is a C4 Lysyl Hydroxylase and is considered playing a broad role in transcription termination [54], the maintenance of embryonic stem cell (ESC) and the development of embryo [55].…”
Section: Discussionmentioning
confidence: 99%
“…Already some inhibitors for Aurora B are in clinical trial phases (this can be further reviewed in Colón-Marrero et al. 24 ) Also, some studies have shown a role for some of these kinases in EMT and metastasis in breast cancer. For example, Aurora B has been shown to induce EMT via OCT4/AKT/GSK3β/Snail1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…19–23 SGO1 is a common target of these kinases. 24 However, the exact mechanism of how E2F3 and SGO1 regulate EMT in TNBC remains poorly understood. Hence, we investigated the effects of E2F3 and SGO1 depletion in EMT, cell invasion, and cell migration in TNBC to dissect the underlying mechanism behind this observation.…”
Section: Introductionmentioning
confidence: 99%